Detrusorrhaphy and Intrafascial Nerve-Sparing During Robot-Assisted Radical Prostatectomy on Recovery of Continence and Potency: Surgical Feasibility, One-Year Functional and Oncologic Outcomes - Lee, Yong Seong; Shin, Tae Young (Urology Journal, 2020)
Purpose: To report the 1-year functional outcomes, oncologic outcomes, and postoperative complications in patients who underwent modified robot-assisted radical prostatectomy (RARP) procedures for achieving early recovery of continence and potency postoperatively. Materials and Methods: This study included 165 patients who underwent RARP. Overall, 98 patients underwent RARP using our modified detrusorrhaphy and intrafascial nerve-sparing techniques (group 1) and 67 underwent standard RARP (group 2). Continence and potency rates were assessed at 1 week, 1, 3, 6, and 12 months after RARP. Oncologic outcomes comprised positive surgical margins (PSMs) and biochemical recurrence (BCR) rate. Results: The continence rates were 61.2% and 6.0%, 72.5% and 11.9%, 79.6% and 20.9%, 91.8% and 58.2%, and 97.9% and 74.6% at 1 week, 1, 3, 6, and 12 months in group 1 and 2, respectively. The potency rates were 66.3% and 11.9%, 78.6% and 38.8%, 85.7% and 50.8%, 92.9% and 70.2%, and 95.9% and 79.1% at 1 week, 1, 3, 6, and 12 months in group 1 and 2, respectively. Overall postoperative complication rates (< 10%) were similar between the groups. The PSMs rate was 17.4% and 16.4% in the two groups. The rate of PSMs in the cohort of patients with stage pT2 disease decreased to 13.6% and 12.5% in groups 1 and 2, respectively. BCR rate was 5.1% and 6.0% in groups 1 and 2, respectively. Conclusion: The use of detrusorrhaphy and intrafascial nerve-sparing techniques is safe and feasible, with our results demonstrating early return to continence and potency. Further studies should be conducted.